Inhibition of Thioredoxin Reductase by Santamarine Conferring Anticancer Effect in HeLa Cells - Zhang, Junmin; Xu, Qianhe; Yang, Hong-Ying; Yang, Minghao; Fang, Jianguo; Gao, Kun (Frontiers in Molecular Biosciences, 2021)
Natural products frequently have unique physiological activities and new action mechanisms due to their structural diversity and novelty, and are an important source for innovative drugs and lead compounds. We present herein that natural product santamarine targeted thioredoxin reductase (TrxR) to weaken its antioxidative function in cells, accompanied by accumulation of high levels of reactive oxygen species (ROS), and finally induced a new mechanism of tumor cell oxidative stress-mediated apoptosis. TrxR knockdown or overexpression cell lines were employed to further evaluate the cytotoxicity of santamarine regulated by TrxR, demonstrated that TrxR played a key role in the physiological effect of santamarine on cells. Santamarine targeting TrxR reveals its previously unrecognized mechanism of antitumor and provides a basis for the further development of santamarine as a potential cancer therapeutic agent.